2013
DOI: 10.3329/jafmc.v8i1.13534
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ketofol (Ketamine Propofol combination) as total intravenous anaesthetic for burn dressing in adult patient

Abstract: DOI: http://dx.doi.org/10.3329/jafmc.v8i1.13534 JAFMC Vol.8(1) 2012 pp.20-24

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Similar results were obtained from other studies. 5,9,10,15 CONCLUSION Following Conclusions are drawn from the Present Study- Both ketamine and fentanyl in propofol infusion for short surgical procedures are equally safe and efficacious.  Infusion of propofol-ketamine and propofol-fentanyl both provides stable haemodynamics and good recovery profile.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Similar results were obtained from other studies. 5,9,10,15 CONCLUSION Following Conclusions are drawn from the Present Study- Both ketamine and fentanyl in propofol infusion for short surgical procedures are equally safe and efficacious.  Infusion of propofol-ketamine and propofol-fentanyl both provides stable haemodynamics and good recovery profile.…”
Section: Discussionmentioning
confidence: 70%
“…Similar results were obtained from other studies. 1,5,8,9,10,12,13 Vallejo M. C. et al 5 also observed no statistical significance in their study. Similar results were obtained from other studies.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The combina on has the less adverse effects than the either drug alone due to their complementary effects of 4 lowering the dose of both drugs. Ketamine is a strong analgesic which effec vely reduces the injec on pain of 14 propofol by a enua ng the afferent pain pathways.…”
Section: Discussionmentioning
confidence: 99%